DISPENSASI NIKAH DALAM UNDANG-UNDANG NOMOR 1 TAHUN 1974 DAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 - Reni Nuraeni; Mustopa Kamal; Ila Nurmila (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
In Law No. 1 of 1974 concerning Marriage, there is a regulation regarding the age of marriage, namely Article 7 Paragraph 1 which states that marriage is permitted if the man has reached the age of 19 years and the woman is 16 years. However, in other articles there are exceptions, namely being allowed to marry under the stipulated age provided there is parental consent and dispensation from the court as stipulated in article 7 Paragraph 2. However, on the other hand, Law No. 35 of 2014 concerning Child Protection provides regulations by requiring parents to prevent marriage at the age of children as stated in Article 26 Paragraph 1 letter c. Every child who is not yet 18 years old must receive protection for their rights and welfare. Therefore, dispensation in a marriage is a phenomenon that must receive serious attention, because this will have an impact on the achievement of the goal of marriage, namely the realization of the sakinah mawaddah warahmah family. This study uses a descriptive analysis method with a normative juridical approach, namely a statute approach, with a research starting point for analysis of statutory regulations. While the data collection technique used is library research (library research) by utilizing various libraries that are relevant to the social phenomena under study. This research resulted in the following conclusions: 1) Marriage dispensation in Law No.1 of 1974 concerning Marriage is contained in Article 7 Paragraph 2, namely in case of deviations from paragraph 1 of this article, dispensation may be requested from the Court or other official appointed by the two parents; 2) One of the child protections in Law no. 35/2014 concerning Child Protection as stated in Article 26 Paragraph 1 letter c, namely that parents are obliged and responsible to prevent marriage at the age of children with the aim of realizing children's welfare through child protection; 3) The two regulations are contradictory, even though the two laws were made by the same legal entity, namely the DPR. This means that there must be a synchronization of the regulations of the two regulations that apply in Indonesia, considering that children are an important and main asset for the survival of life.